Serum lipid profile in adolescents and adults with acne vulgaris receiving isotretinoin - Kaveh Gharaei Nejad; Abbas Darjani; Narges Alizadeh; Seyede Tahoura Hakemzadeh; Afagh Hassanzadeh Rad; Ehsan Kazemnejad-Leili; Reyhaneh Ghadarjani; Hojat Eftekhari; Rana Rafiei; Setila Dalili (Babol University of Medical Sciences, 2024)
Background: Acne vulgaris is a chronic, inflammatory disease and one of the most common skin diseases. Isotretinoin is the best treatment for severe nodulocystic acne compared to other systemic medicine. Although serum lipids elevation is one of the side effects of this medicine; recent studies have shown controversial results. This study aimed to assess the serum lipid profile in adolescents and adults with acne vulgaris receiving isotretinoin. Methods: This is a cross-sectional study on 65 adolescents and adults older than 16 years old (55 females and 10 males) with moderate to severe degrees of acne vulgaris under a fixed low dose of 20 mg/day Isotretinoin treatment for 120 days. We analyzed the data using the SPSS software Version 16 using paired sample t-test, Wilcoxon, and ANCOVA test. Results: In this study, 65 records of patients with a mean age of 22.21±6.25 years were assessed. There was a significant elevation in Cholesterol and LDL levels, but in HDL and triglyceride levels no significant change occurred. A significant change in cholesterol levels was noticed in the adolescent age group, the female sex, and the normal weight group. Triglyceride had a significant change in the female sex and normal weight group and HDL significantly increased in male patients. Conclusion: Although a low dose of isotretinoin can be used with minimal concern for changes in lipid profile in acne vulgaris patients, in the long-term follow-up and treatment, it seems that we have to administer it cautiously.